Prophylaxis for acute exacerbations of chronic bronchitis using an antibacterial sublingual vaccine obtained through mechanical lysis: a clinical and pharmacoeconomic study - Cogo, R.; Ramponi, A.; Scivoletto, et al., G. (Acta Biomedica Atenei Parmensis, 2003)
Chronic obstructive bronchitis (COB) complicated by acute exacerbations, or exacerbations, triggered by episodes of infection is the most demanding respiratory disease in our country today, to the extent that the implementation of every possible prevention strategy, in terms of both behaviour and prophylactic vaccination, is fully justified. From this point of view, in addition to the classic anti-viral vaccines, increasing importance is also being placed on antibacterial vaccines obtained by mechanically crushing pathogen bacteria (without the use of chemicals to denature the antigenic structures), which can be sublingually administered. In this study, conducted on 57 patients aged over 75 suffering from COB and affected by at least one exacerbation over the past 12 months, we evaluated the incidence of these exacerbations during a follow-up period, subsequent to prophylaxis with polyvalent bacterial mechanical lysate. As well as the absolute number of episodes, we also evaluated the seriousness of the episodes, the length of any antibiotic therapy and the overall cost of this therapy and of the prophylactic treatment.We then compared this data with that of the same period for the previous year, during which time no antibacterial prophylaxis had been administered. Both the absolute number of exacerbations, their length and seriousness were shown to be significantly reduced during the period of treatment compared to the control period. Similarly, the need to use antibiotic treatments, as well as the overall cost of the treatment of these patients, were shown to be reduced during the period of treatment compared to the control period.